Tinjauan Fatwa DSN-MUI No 44/DSN-MUI/VIII/2004 Terhadap Akad Ijarah Multijasa Dalam Pembiayaan Pernikahan - Nur Izzah; Refi Malinda (JURNAL ILMIAH NUSANTARA, 2026)
The factor that causes people who are not ready to get married is that the cost of marriage is too expensive because marriage is considered a precious moment in life so that this marriage wants to be held luxuriously and festively. With the existence of wedding financing using a multijasa ijarah contract, it helps those who want to get married but lack funds. However, there is a difference of opinion according to Ibn Mas'ud and Shaykh Muhammad bin Shalih Al-Uthaimin regarding this wedding financing. This research uses qualitative research in the form of a case study with a normative approach. The research results show that (1) the practice used by the institution is to use an ijarah contract where the BMT is a service provider for customers in need and the BMT will conduct lease transactions with those who rent goods because the customer is not given cash by the BMT and the BMT represents the customer to pay the rent. (2). The practice applied by the BMT institution is in accordance with the fawa DSN-MUI Number 44/DSN-MUI/VIII/2004.